Efficient, solvent-free method for the chemoselective synthesis of acylals from aldehydes and their deprotection catalyzed by silica sulfuric acid as a reusable solid acid catalyst - Desai, Uday V.; Thopate, T. S.; Pore, D. M.; Wadgaonkar, P. P. (Catalysis Communications, 2006)
An efficient method has been developed for the chemoselective synthesis of acylals from aldehydes and acetic anhydride in the presence of silica sulfuric acid as a reusable solid acid catalyst under solvent-free conditions. Ketones are found to remain unaffected under the reaction conditions. The deprotection of acylals has also been achieved using SSA in methanol medium. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Acylals; aldehydes; Chemoselective; protection and deprotection silica sulfuric acid